Legal Protection of Women in the Divorce Process: Case Studies and Policy Implications in Indonesia - Trikusuma, Sultoni; Muhlizar, Muhlizar (Faculty of Law, Universitas Pekalongan, 2024)
The objective of this investigation is to examine the legal safeguards available to women in the Indonesian divorce procedure, with a particular emphasis on case studies and the existing policy implications. A qualitative approach was utilized in conjunction with a comprehensive literature review in order to gain an in-depth understanding of existing policies, regulations, and protections pertaining to women's rights in the context of divorce. Data were gathered via an analysis of legal documents, academic literature, and interviews with legal experts and women's rights activists. The findings indicated that despite the existence of a legal framework that supports women in divorce proceedings, there are still significant obstacles to the implementation of these rights at the local level. These obstacles are mainly attributed to gaps in legal understanding, patriarchal cultural norms, and limited resources. The research proposes the expansion of legal awareness initiatives within communities and the introduction of policy reforms that are more inclusive to guarantee gender equity in divorce procedures.